Manure and lagoon nutrients from dairies using flush systems - Strahm, T.D.; Harner, Joseph P.; Key, David V.; Murphy, James P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nine primar,y lagoons and solids storage basins were sampled on Kansas dairies using flush systems. These samples were analyzed for nutrient content of wastewater and sand manure. The manure moisture content in the storage basins averaged 81%. The average totals of nitrogen, phosphate, and potash were 3450, 1345, and 1420 mg/L, respectively, for flushing systems. The average totals of nitrogen, phosphate, and potash in the lagoon samples were 816, 337, and 1134 mg/L, respectively, for dairies using recycled water for flushing alleys. These data and previously reported data indicate that lagoon effluent and manure removed from basins must be managed differently between dairies using flush versus scrape systems.
Keywords: Dairy; Manure; Nutrients; Sands; Lagoons